Adult inclusion conjunctivitis diagnosed by polymerase chain reaction and Giemsa stain. (2022) - Lee, Wan-Ju Annabelle; Chen, Chien-Chin
Highlights: Chlamydial conjunctivitis may mimic as allergic or chronic conjunctivitis. Careful history taking helps make correct diagnosis. Chlamydial conjunctivitis may be diagnosed by PCR of conjunctival lavage. Giemsa stain of conjunctival lavage also confirms diagnosis. Abstract: Adult inclusion conjunctivitis, caused by Chlamydia trachomatis, is easily underdiagnosed with nonspecific ocular manifestation. Combined scrape cytology and molecular testing may be a useful strategy for its early diagnosis. A 24-year-old healthy male complained of blurred vision, foreign body sensation, and watery discharge in his right eye for four weeks. His visual acuity was 20/20 bilaterally at his first visit. Allergic conjunctivitis was the first impression, and topical treatment with corticosteroid and anti-histamine was prescribed. However, he returned five days later without symptom improvement, and his right eye vision declined to 20/40. Subepithelial corneal infiltration of his right eye was observed. According to his personal history, his girlfriend was diagnosed with sexually transmitted chlamydial infection and genital gonorrhea. Under the suspicion of sexually transmitted adult inclusion conjunctivitis, we collected his conjunctival lavage to both real-time polymerase chain reaction, which proved chlamydial infection, and Giemsa stain, which demonstrated typical basophilic intracytoplasmic inclusions. To diagnose adult inclusion conjunctivitis, we can use real-time polymerase chain reaction or Giemsa stain to help us obtain a quick and correct diagnosis.